2016
DOI: 10.1261/rna.057810.116
|View full text |Cite
|
Sign up to set email alerts
|

ATPγS stalls splicing after B complex formation but prior to spliceosome activation

Abstract: The ATP analog ATPγS inhibits pre-mRNA splicing in vitro, but there have been conflicting reports as to which step of splicing is inhibited by this small molecule and its inhibitory mechanism remains unclear. Here we have dissected the effect of ATPγS on pre-mRNA splicing in vitro. Addition of ATPγS to splicing extracts depleted of ATP inhibited both catalytic steps of splicing. At ATPγS concentrations ≥0.5 mM, precatalytic B complexes accumulate, demonstrating a block prior to or during the spliceosome activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The Prp39-Prp42 heterodimer binds Yhc1 to anchor the U2 snRNP 3' domain to the U1 snRNP. Similar interactions were observed biochemically between the human alternative splicing factor PRPF39 homodimer and U1C12 (yeast Yhc1), suggesting that PRPF39 may likewise contact the human U2 3' domain, though it is not an obligate component of the human A complex20 (Fig. 2a).…”
supporting
confidence: 65%
“…The Prp39-Prp42 heterodimer binds Yhc1 to anchor the U2 snRNP 3' domain to the U1 snRNP. Similar interactions were observed biochemically between the human alternative splicing factor PRPF39 homodimer and U1C12 (yeast Yhc1), suggesting that PRPF39 may likewise contact the human U2 3' domain, though it is not an obligate component of the human A complex20 (Fig. 2a).…”
supporting
confidence: 65%
“…Interestingly, in human Prp2 (DHX16) the most N-terminal tip of the corresponding domain has been proposed to contain a PWI-like domain, which is also present in the spliceosomal helicases Brr2 (U5-200K) and has been predicted for Prp22 (DHX8) (Absmeier et al, 2015;Korneta et al, 2012). In Brr2 the PWI-like domain-containing N-terminal region has been proposed to act as a structural switch autoinhibiting Brr2 via substrate competition and conformational clamping (Absmeier et al, 2015;Agafonov et al, 2016;Nguyen et al, 2016). In the absence of detailed structural and biochemical information on the N-terminal extension of Prp2, one can only speculate about the functional role of this domain.…”
Section: Discussionmentioning
confidence: 99%
“…Many splicing regulatory factors and general splicing factors purify with SWI/SNF subunits (Zhao et al, 1998;Dellaire et al, 2002) and purifications of the snRNP U2 spliceosome component also include several SWI/SNF subunits (Makarov et al, 2012;Allemand et al, 2016). We performed an analysis of BRG1 and BRM interacting proteins in the RNP fraction and it revealed that BRG1, in particular, interacted with U2 snRNP and U5-U6 snRNP factors that assemble early in the splicing cycle (Lardelli et al, 2010;Hegele et al, 2012;Agafonov et al, 2016;Haselbach et al, 2018). In addition to general splicing factors, we also found that BRG1 interacted with many regulatory RNA binding factors, such as hnRNPs and RNA helicases.…”
Section: Discussionmentioning
confidence: 90%